2017
DOI: 10.1017/s1368980017003433
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy and the double burden of malnutrition: cross-national longitudinal analysis of minimum wage and women’s underweight and obesity

Abstract: The present longitudinal multi-country study showed that a $10 rise in monthly minimum wage significantly accelerated the decline in women's underweight prevalence, but had no association with the pace of growth in obesity prevalence. Thus, modest rises in minimum wage may be beneficial for addressing the protracted underweight problem in poor countries, especially South Asia and parts of Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Another important point is that, like many other countries that have focused on obesity and its adverse health outcomes, the issue and consequences of being underweight in many subpopulations has largely been overshadowed in Iran too (27,28). The alarming burden caused by malnutrition in females of reproductive age, pregnant females, and children, must lead to interventions focused on prompt problem-based solutions (27,28). In order to manage the problem, social and food policies must include practical policies and strategies that enhance food security, especially among poor households.…”
Section: Discussionmentioning
confidence: 99%
“…Another important point is that, like many other countries that have focused on obesity and its adverse health outcomes, the issue and consequences of being underweight in many subpopulations has largely been overshadowed in Iran too (27,28). The alarming burden caused by malnutrition in females of reproductive age, pregnant females, and children, must lead to interventions focused on prompt problem-based solutions (27,28). In order to manage the problem, social and food policies must include practical policies and strategies that enhance food security, especially among poor households.…”
Section: Discussionmentioning
confidence: 99%
“…Conklin and coworkers [11] developed separate multilevel models to estimate the impact of a US $10 increase in monthly minimum wage in 24 low-income countries and reported a significant association with an accelerated decline in women's underweight prevalence but observed no impact on the pace of growth in obesity prevalence [11].…”
Section: Regional Changes In Minimum Wagementioning
confidence: 99%
“…These two studies highlighted the differential impact of national programmes and underscored the need for context-specific, tailored interventions to eradicate vitamin A deficiencies to prevent underconsumption of the vitamin as well as its excessive intake, which can increase the risk of bone demineralisation and fractures [21,22]. Two distinct modelling studies have shown the potential utility two tools-the culturally adapted linear programming tool and the US$10 minimum wage increase-to advise national programs [10,11]. Nevertheless, it is noteworthy that whilst the culturally adapted linear programming tool to design diets at minimum cost for low-income Ghanaian families is expected to address a low intake of micronutrients (iron, iodine, vitamin A, and folic acid) as well as obesity and diet-related NCDs, a poverty-reduction approach consisting of a minimum wage increase was shown to be insufficient to tackle obesity in this modelling study.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…14 Evidence examining the association between higher minimum wages and obesity range from modestly negative to modestly positive. 12,[15][16][17][18][19][20][21][22] Minimum wage has also been associated with a reduction in the prevalence of underweight in women 22 and markers of malnutrition in children. 23 Two studies have provided countervailing evidence in the evaluation of higher minimum wages and fruit and vegetable consumption with one concluding it decreases consumption 21 and the other that it increases consumption.…”
Section: Introductionmentioning
confidence: 99%